HUBUNGAN KELINCAHAN TERHADAP KETERAMPILAN DRIBBLING BOLA BASKET PADA PEMAIN CLUB ES-PE-DE KOTA LUBUKLINGGAU - Bima Citra Wicaksono; Rais Firlando; Hengky Remora (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the relationship of agility to dribbling skills in ES-PE-DE club players in Lubuklinggau City. The method used is simple correlation. The sample consisted of 10 people with the sampling technique using saturated sampling. Collecting data in this study used the dogging run test for variable X and basketball dribbling test for variable Y. The data analysis technique used the following steps: normality test, poduct moment correlation test. The results of data analysis show that the value of rcount> rtable is 0.694> 0.632 and the value of tcount> ttable is 2.727 > 1.860. It can be concluded that there is a significant relationship between agility towards basketball dribbling skills in ES-PE-DE club players in Lubuklinggau City, with a relationship percentage of 48.16%.